Has the “green” transformation of the Common Agricultural Policy affected the environmental sustainability of farms? - Aleksandra Pawłowska (PLoS ONE, 2025)
This study aims to quantify the level of environmental sustainability in EU farms using a synthetic measure of the environmental burden in agriculture and to assess the overall effectiveness of the “green” transformation of the Common Agricultural Policy (CAP) in enhancing farm sustainability. The Environmental Burden Index (EBI) was calculated for the average farm in a region using the TOPSIS method. The research hypothesis under investigation posits that environmental subsidies have contributed to a reduction in the environmental burden of agriculture. A panel regression model was estimated based on regional data from the EU FADN database covering the period 2004–2022 to identify the extent to which the “green” CAP transformation has impacted the environmental sustainability of farms. The research identified the EU regions that impose the lowest environmental burden in agriculture, with the leading regions primarily located in Italy. Furthermore, the estimated models revealed which types of subsidies benefit and hinder the environmental sustainability of farms. Notably, environmental subsidies were found to have a particularly positive impact on the EBI.